KEGIATAN KOLASE TIGA DIMENSI TERHADAP KEMAMPUAN MOTORIK HALUS ANAK AUTIS DI TK - Kurnia Herviani, Vivi (Jurnal Pendidikan Khusus, 2017)
ABSTRACT A fine motoric ability required to be developed for the autism children because it required in doing learning activity and daily activity. The fine motoric aspects that should be developed in this research were handling, pinching, holding, rolling, and attaching things. The learning activity used to enhance the fine motoric ability was by three dimensions collage activity through activity steps from the start till the end. The subjects in this research were autism children who were five to seven years old numbering seven children in TK Mentari School Sidoarjo. The purpose of this research was to prove whether there was influence of three dimensions collage activity toward fine motoric ability to autism children in TK Mentari School Sidoarjo or not. The method of this research was quantitative kind and the data which was collected using participant’s observation was used to obtain the data of fine motoric ability to autism children before and after giving treatment. The research result was obtained from the pre-test result and post-test result. It was obtained that the pre-test result was 41,33 and the post-test result was 79,08. In this way, it could be concluded that Z counted = 2,28 was compared to critic value 5% Z table = 1,96. The result showed Z counted was greater than Z table (Zh > Zt) which meant that Ho was refused and Ha was accepted so it could be stated that there was significant influence of three dimensions collage activity application toward fine motoric ability to autism children in TK Mentari School Sidoarjo.   Keywords: three dimensions collage, fine motoric ability